2018
DOI: 10.1159/000495057
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of the Transcriptome and Proteome of Comte de Paris and Smooth Cayenne to Improve the Understanding of Ethephon-Induced Floral Transition in Pineapple

Abstract: Background/Aims: Ethylene is usually used to induce floral transition in pineapple. However, its successful induction in plants categorized as Cayenne is difficult or completely ineffective, and information concerned is limited. The present study was undertaken to investigate the molecular mechanisms underlying this obstacle. Methods: Transcriptome and proteome comparative analyses were performed to explore the important regulation and pathway variations after ethephon induction in the induction-easy ‘Comte de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The stigma is trifid, and the style forms a narrow and compact tube structure that is longer than the stamens 6 . Previous studies have investigated the molecular basis of the floral transition in pineapple 7 , 8 , and several genes such as FLOWERING LOCUS T ( FT ), LEAFY ( LFY) , PISTILLATA ( PI ), FT-LIKE , and AP1-LIKE ( APETALA1 ) have been shown to regulate floral meristem identity and floral morphogenesis 9 11 . However, the molecular mechanisms underlying pineapple floral organ development have yet to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The stigma is trifid, and the style forms a narrow and compact tube structure that is longer than the stamens 6 . Previous studies have investigated the molecular basis of the floral transition in pineapple 7 , 8 , and several genes such as FLOWERING LOCUS T ( FT ), LEAFY ( LFY) , PISTILLATA ( PI ), FT-LIKE , and AP1-LIKE ( APETALA1 ) have been shown to regulate floral meristem identity and floral morphogenesis 9 11 . However, the molecular mechanisms underlying pineapple floral organ development have yet to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…These differences for the period from planting to the beginning of the harvest are in agreement with studies conducted in other regions (Kist et al, 2011), showing the possibility of using ethephon for pineapple production scheduling also in the north of Espírito Santo state. Liu et al (2018) suggested that the induction with ethephon triggered the photoperiodic pathway for flower initiation, therefore, explaining the independent flowering of the inductive photoperiod. Ethephonmediated induction probably mimics the process of vernalization in the floral transition, increasing the expression, and promoting a positive regulation of the floral meristem identity genes involved in flower development (Liu & Fan, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…From domestic and international research, there are relative research we can learn methods and technologies for use in further experiments. For example, validating the genes related to resistance of pineapple in Arabidopsis [ 65 , 66 ], studying the molecular mechanisms of resistance in pineapple through transcriptomic and metabolomic analyses [ 67 – 70 ], analyzing resistance mechanisms through the expression of genes [ 71 ], studying the regulation of resistance of Arabidopsis thaliana by pineapple-related kinase gene [ 11 , 65 ], studying the regulation ability of beneficial elements on plant tolerance to abiotic stress [ 72 ], studying the effect of combining lipoic acid and melatonin against oxidative stress [ 73 ], studying the effect of melatonin against abiotic stress [ 74 ], studying the ability of other PGRs to alleviate drought stress in rice.…”
Section: Discussionmentioning
confidence: 99%